MODIFICATION OF DIESEL ENGINE TO PRODUCER GAS ENGINE - Aung, Nay Zar (Agency for the Assessment and Application of Technology)
This paper describes considerations and procedure of conversion from diesel engine to producer gas engine. In this paper, the performance of producer gas engine is compared to the original diesel engine and the factors affecting on performance of the producer gas engine are mentioned. After converting the 26.5 kW diesel engines to producer gas engine, the power output of producer gas engine is 40% less than that of original diesel engine. However producer gas engines are used for saving fuel cost and more economic for long time span. The comparison based on 8 kW electricity output that running for 4 hours in a day found that fuel cost for producer gas engine is Ks (Kyats) 2167 and the fuel cost for diesel engine is Ks.(Kyats) 7680, this means save cost of Ks (Kyats) 2008960 along the engine life span.